2017
DOI: 10.1142/s0218216517400107
|View full text |Cite
|
Sign up to set email alerts
|

Large random simplicial complexes, III the critical dimension

Abstract: In this paper we study the notion of critical dimension of random simplicial complexes in the general multi-parameter model described in [8], [9], [10]. This model includes as special cases the Linial-MeshulamWallach model [19], [20] as well as the clique complexes of random graphs. We characterise the concept of critical dimension in terms of various geometric and topological properties of random simplicial complexes such as their Betti numbers, the fundamental group, the size of minimal cycles and the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 17 publications
1
56
0
1
Order By: Relevance
“…It was shown that the Betti numbers have a very specific pattern which can be described using the notion of a critical dimension k * . Roughly, it was established in [5] that homologicaly a random simplicial complex in the lower model can be well approximated by a wedge of spheres of dimension k * .…”
Section: The Notion Of Critical Dimension In the Lower Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that the Betti numbers have a very specific pattern which can be described using the notion of a critical dimension k * . Roughly, it was established in [5] that homologicaly a random simplicial complex in the lower model can be well approximated by a wedge of spheres of dimension k * .…”
Section: The Notion Of Critical Dimension In the Lower Modelmentioning
confidence: 99%
“…In the present paper we study two very general probabilistic models generating random simplicial complexes of arbitrary dimension which we call the lower and upper models. random simplicial complexes was studied in a series of papers [2], [3], [4], [5] under the name of multiparameter random simplicial complexes; the name reflects the fact that the geometric and topological properties of simplicial complexes in this model depend on the set of probability parameters p 0 , p 1 , . .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that most random complexes which appear in literature are homogeneous. For example the multi-parameter random simplicial complexes of [6], [7], [8], [9] are homogeneous lower random simplicial complexes.…”
Section: 2mentioning
confidence: 99%
“…Consider the dual system of probability parameters p ′ σ = 1 − pσ (see (10)) which satisfies 0 < e −A ′ = 1 − P ≤ p ′ σ ≤ 1 − p = e −a ′ < 1, where a ′ and A ′ are defined in (13). Next, we use the isomorphism c of Theorem 2.2 and the duality for the Betti numbers (9). The complex c(Y ) is a random simplicial complex in the lower model with respect to the system of probability parameters p To prove the third statement we observe that the reduced Betti numbers of c(Y ) vanish in all dimensions except possibly log 2 ln n − log 2 A ′ − 1 − δ 0 < j ≤ log 2 ln n + log 2 log 2 ln n − log 2 a ′ − 1 + ǫ 0 , Since b j (Y ) = b n−2−j (c(Y )) (cf.…”
Section: Proof Of Theorem 32mentioning
confidence: 99%